COMPARATIVE STUDY OF ARAB LANGUAGE WRITING SKILLS BETWEEN STUDENTS GRADUATED FROM JUNIOR HIGH SCHOOL AND MTS IN CLASS XI MA DARUL AMAN LENGKESE TAKALAR - Agung Sedayu M; Ambo Dalle; Ahmad Sirfi Fatoni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Agung Sedayu M, Comparative Study of Arabic Writing Skills between Junior High School and Middle School Graduates in Class XI of MA Darul Aman Lengkese Takalar. Thesis. Department of Foreign Language Education. Arabic Language Education. Faculty of Language and Literature, Makassar State University (supervised by Ambo Dalle and Ahmad Sirfi Fatoni). This study aims to determine the comparison of Arabic writing skills between junior high school and high school graduates in class XI of MA Darul Aman Lengkese Takalar in the 2025/2026 academic year. This research is a quantitative research using a comparative approach. The techniques used in this research are observation techniques, documentation, tests from two different samples, namely junior high school graduates totaling 14 people with MTS graduates totaling 14 people with a total sample of 28 people. The results of this study showed that the average value of the Arabic writing skills test results of junior high school graduates got an average result of 54.9 while MTS graduates obtained an average value of 62.74. Based on the results of the t-test conducted, there is a significant difference between the Arabic writing skills of junior high school graduates and MTS graduates in class XI MA Darul Aman Lengkese Takalar.